2014
DOI: 10.1016/j.rvsc.2013.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Oral Recombinant Feline Interferon-Omega as an alternative immune modulation therapy in FIV positive cats: Clinical and laboratory evaluation

Abstract: Recombinant-Feline Interferon-Omega (rFeIFN-ω) is an immune-modulator licensed for use subcutaneously in Feline Immunodeficiency virus (FIV) therapy. Despite oral protocols have been suggested, little is known about such use in FIV-infected cats. This study aimed to evaluate the clinical improvement, laboratory findings, concurrent viral excretion and acute phase proteins (APPs) in naturally FIV-infected cats under oral rFeIFN-ω therapy (0.1 MU/cat rFeIFN-ω PO, SID, 90 days). 11 FIV-positive cats were treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
26
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 21 publications
4
26
0
Order By: Relevance
“…Furthermore, there was no significant difference between the SC high dose historical control group and the PO medium-high dose group, suggesting that oral administration of IFN-ω in a lower dose could be used as an alternative to the licensed protocol at reduced cost (EBM grade III). 120 In a recently published study that assessed viraemia, provirus load and blood cytokine profile in naturally FIV-infected cats treated either with oral or subcutaneous feline IFN-ω (in the same dosages described above), but again without placebo control, there was no change in viraemia or in most of the cytokine levels measured (EBM grade III), 121 which questions the efficacy noted in previous clinical trials without placebo control. The fact that virus load remained unchanged in the cats, but some clinical improvement could be observed, invites the conclusion that IFN-ω might have an effect on secondary infections rather than on FIV itself.…”
Section: Conflict Of Interestmentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, there was no significant difference between the SC high dose historical control group and the PO medium-high dose group, suggesting that oral administration of IFN-ω in a lower dose could be used as an alternative to the licensed protocol at reduced cost (EBM grade III). 120 In a recently published study that assessed viraemia, provirus load and blood cytokine profile in naturally FIV-infected cats treated either with oral or subcutaneous feline IFN-ω (in the same dosages described above), but again without placebo control, there was no change in viraemia or in most of the cytokine levels measured (EBM grade III), 121 which questions the efficacy noted in previous clinical trials without placebo control. The fact that virus load remained unchanged in the cats, but some clinical improvement could be observed, invites the conclusion that IFN-ω might have an effect on secondary infections rather than on FIV itself.…”
Section: Conflict Of Interestmentioning
confidence: 97%
“…120 The treatment protocol was 1 x 10 5 IU/cat PO q24h for 90 consecutive days, administered by the cats' owners. A historical group treated subcutaneously with the high dose licensed protocol (1 x 10 6 IU/kg SC q24h) was used as a control for comparison, but no placebo group was included.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…Similar to the licensed protocol, clinical improvement was observed in cats treated with oral rFeIFN-ω [72]. However, hematology, biochemistry profiles and APP profiles did not significantly change in cats following this protocol [72]. Other studies showed that an rFeIFN-ω licensed protocol decreases concurrent viral infections, even if no true changes are observed in FIV viral load.…”
Section: Current Potential Applications Of Type I Ifn Classesmentioning
confidence: 99%
“…rFeIFN-ω therapy seems to be cost-limiting so an alternative oral protocol for FIV-infected cats has been suggested. Similar to the licensed protocol, clinical improvement was observed in cats treated with oral rFeIFN-ω [72]. However, hematology, biochemistry profiles and APP profiles did not significantly change in cats following this protocol [72].…”
Section: Current Potential Applications Of Type I Ifn Classesmentioning
confidence: 99%
See 1 more Smart Citation